The Development of Bahasa Indonesia in Multicultural Context: A Case Study of Adoloscent's Slang - I Dewa Putu Wijana (Humaniora, 2011)
This article deals with Indonesian slang that is commonly used by youngsters as a symbol of their intimate friendship. This colloquial variation, which is often regarded as a threat to the existence of standard Indonesian is in fact very rich with interesting linguistic features, especially in terms of its forms, formation processes, spellings, and sources. The discovery of its uniqueness will hopefully vanish all negative views about the slang because its presence will actually give give contribution for the development of Bahasa Indonesia.